MANAJEMEN PENGEMBANGAN MADRASAH TSANAWIYAH DI MTs. DARUL LUGHAH WAL KAROMAH - Ahmad Syaifuddin; Intan Balqis Humairoh (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2022)
This research aims to find out the steps taken in developing the program at MTs Darul Lughah Wal Karomah which is located in the Sidomukti sub-district, Kraksaan, Probolinggo. In order to find out what are the obstacles or supports for madrasas in improving madrasah development through madrasah management, this research uses a qualitative approach with a case study design. The data in the study were obtained from research informants, namely the head of the madrasah, the head of administrative affairs. Data collection techniques used are interviews, observation and documentation. The results of the study show that 1) The madrasa head has implemented management functions: planning, organizing, implementing, supervising in madrasa management, 2) The existence of madrasa culture is closely related to positive values ​​and norms that bind all madrasa residents, 3) Student acceptance new programs to recruit regular class students and superior classes are carried out to get good input which will produce excellent output. While some of the inhibiting factors include: inadequate infrastructure, lack of electronic facilities owned by madrasahs, teachers who are less creative and innovative in carrying out the learning process in the classroom, teachers who are more concerned with personal matters than focusing on school matters.